Peat briquette as an alternative to cooking fuel: A techno-economic viability assessment in Rwanda - Hakizimana, Jean de Dieu K.; Kim, Hyung-Taek (Energy (Oxford), 2016)
Commercialization of peat briquetting technology was analyzed to know whether the technology is economically viable or not compared to commercialization of charcoal. The investigation of economic viability was assessed from raw-peat production to briquetting technologies. The briquettes were made by naturally dried of peat from Bisika, Bahimba, Ndongozi and Nyirabirande bogs, through a rotary pulverizer and a briquette press; they were carbonized into furnace at 450 °C to reduce its health effects. The burning rate of peat briquettes made varied from 0.178 kg/hour to 0.222 kg/hour. Ash content varying between 3 and 7.2 percent was also observed. The results showed that peat briquettes can be sold at USD0.18 per unit, with a total NPV of USD17.2 million. However, as the NPV tends to be zero, the selling price would be approximately USD0.155 per briquette. Monthly charcoal expenses were about USD23.20/household compared to a per-household cost of USD16.20/month of peat briquettes consumption; the supplanting of charcoal by peat briquettes would help the average Rwandan household reduce its monthly expenses by 30 percent. Peat briquettes utilization as cooking fuel in Rwanda could save 0.05 percent of CO2 and more than 99 percent of CH4 emissions, compared to charcoal emissions. •A technical process for peat production and peat briquetting.•An efficiency test of carbonized briquettes.•Commercialization of peat briquettes is compared to commercialization of charcoal.•Opportunities for greenhouse gas emissions reduction.